(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the lexicographic characteristics of sewing terminology in English and Uzbek. Lexicography, which studies words, their meanings, and structures, plays a significant role in the translation process. Sewing terminology is shaped by both technical and cultural factors, which leads to certain difficulties in lexical representation and translation. Although English sewing terms are widely used globally, their accurate and equivalent translation into Uzbek is not always available. The study highlights the semantic and cultural aspects of sewing terminology through a lexicographic analysis.